Networked selves: Trajectories of blogging in the United States and France - Siles González, Ignacio (2017)
Solo cubierta del libro. Documento relacionado: Tesis "Voicing the Web: The Trajectories of Blogging in the United States and France" http://hdl.handle.net/10669/75155